2015
DOI: 10.1002/prca.201400104
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphoproteomics in the development of personalized cancer therapies

Abstract: Cell signalling pathways driven by protein and lipid kinases contribute to the onset and progression of virtually all cancer types. Consequently, several inhibitors against these enzymes have clinical utility for the treatment of different forms of cancer. A problem that hampers further development is that not all patients respond equally well to kinase inhibitors and a significant proportion of those that initially respond eventually develop resistance. This review considers how an integrative analysis of kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 93 publications
(129 reference statements)
0
30
0
Order By: Relevance
“…Based on its potential to provide insight in tumor signaling pathways and potential drug targets, MS-based quantitative phosphoproteomics of tumor tissues has been suggested as a method for selection of protein kinase inhibitors in individual patients with cancer [12,20,21]. To enable clinical implementation of this approach for personalized medicine the phosphoproteomics workflows should be compatible with clinically available sample amounts such as needle biopsies and reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on its potential to provide insight in tumor signaling pathways and potential drug targets, MS-based quantitative phosphoproteomics of tumor tissues has been suggested as a method for selection of protein kinase inhibitors in individual patients with cancer [12,20,21]. To enable clinical implementation of this approach for personalized medicine the phosphoproteomics workflows should be compatible with clinically available sample amounts such as needle biopsies and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Drawbacks of this approach are the limited number of phosphosite-specific antibodies targeting assumed epitopes of interest [20,38]. In contrast, the 'unbiased' analysis of the signaling network by MS-based phosphoproteomics we used here may benefit the development of personalized therapies [12]. …”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…In rectal cancers of the same pathological differentiation, alternative splicing of a gene may lead to different resistances to various treatments, including CRT. Haley et al and Cutillas et al reported that phosphoproteomics enabled tumor cells to survive against chemotherapeutics (27,28). However, the septin complex was the major annotated function among Figure 3.…”
Section: Discussionmentioning
confidence: 99%